Uterine clinical findings, fertility rate, leucocyte migration, and COX-2 protein levels in the endometrial tissue of susceptible mares treated with platelet-rich plasma before and after AI - Segabinazzi, Lorenzo G. [UNESP]; Friso, Aime M. [UNESP]; Correal, Sebastian B.; Crespilho, André M.; Dell'Aqua, José Antonio [UNESP]; Miró, Jordi; Papa, Frederico O. [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2017)
Persistent mating-induced endometritis (PMIE) results in decreased fertility in horses, thereby causing a significant impact in the horse market. Platelet-rich plasma (PRP), a modulator of the inflammatory response, has been largely used in veterinary medicine. Here, we investigated the effects of PRP on uterine inflammation, conception rate, endometrial polymorphonuclear neutrophil (PMN) migration, and COX-2 protein levels in the endometrial tissue. Thirteen PMIE-susceptible mares were used for artificial insemination (AI). The mares were inseminated with fresh semen in three consecutive cycles in a cross-over study design. The following cycle classifications were used: control cycle, no pharmacological interference; pre-AI, 20 mL of PRP was infused 24 h before AI; and post-AI, 20 mL of PRP was infused four h after AI. Follicular dynamics were monitored daily by transrectal ultrasound. When a follicle larger than 35 mm was detected, ovulation was induced with deslorelin acetate (1 mg, im). AI was performed 24 h after ovulation induction. Intrauterine fluid (FLU) was evaluated by ultrasonography before and 24 h after AI. PMNs in uterine cytology (CYT) and biopsy (HIS) were also observed before and 24 h after AI. Pregnancy was determined within 14 days after ovulation. Number of COX-2 positive cells was evaluated by immunohistochemistry. Both PRP treatments resulted in a decrease of PMNs in the CYT after breeding when compared to controls. FLU did not differ between cycles; however, the conception rates were significantly higher in the PRP mares. Mares positive for endometritis decreased in both treatment groups, and a more intense positive COX-2 labeling was observed in the control group when compared to the two treatment groups. In conclusion, PRP beneficially reduces inflammatory response in PMIE mares independent of when treatments were administered, thus increasing chances of successful pregnancy.
Keywords: Embryo transfer; Endometritis; Equine; Platelet-rich plasma